Regional siderosis: a new challenge for iron chelation therapy - Cabantchik, Zvi I.; Munnich, Arnold; Youdim, Moussa B.; Devos, David (Frontiers in Pharmacology, 2013)
The traditional role of iron chelation therapy has been to reduce body iron burden via chelation of excess metal from organs and fluids and its excretion via biliary-fecal and/or urinary routes. In their present use for hemosiderosis, chelation regimens might not be suitable for treating disorders of iron maldistribution, as those are characterized by toxic islands of siderosis appearing in a background of normal or subnormal iron levels (e.g. sideroblastic anemias, neuro- and cardio-siderosis in Friedreich ataxia- and neurosiderosis in Parkinson’s disease). We aimed at clearing local siderosis from aberrant labile metal that promotes oxidative damage, without interfering with essential local functions or with hematological iron-associated properties. For this purpose we introduced a conservative mode of iron chelation based on dual activity based on scavenging labile metal but also redeploying it to cell acceptors or to physiological transferrin. The “scavenging and redeployment” mode of action was designed both for correcting aberrant iron distribution and also for minimizing/preventing systemic loss of chelated metal. We first examine cell models that recapitulate iron maldistribution and associated dysfunctions identified with Friedreich ataxia and Parkinson’s disease and use them to explore the ability of the double-acting agent deferiprone, an orally active chelator, to mediate iron scavenging and redeployment and thereby causing functional improvement. We subsequently evaluate the concept in translational models of disease and finally assess its therapeutic potential in prospective double-blind pilot clinical trials. We claim that any chelator applied to diseases of regional siderosis, cardiac, neuronal or endocrine ought to preserve both systemic and regional iron levels. The proposed deferiprone-based therapy has provided a paradigm for treating regional types of siderosis without affecting hematological parameters and systemic functions.